Stimulation of IL-6 Cytokines in Fibroblasts by Toll-like Receptors 2 - Souza, Pedro Paulo Chaves de [UNESP]; Palmqvist, P.; Lundgren, I.; Lie, A.; Costa-Neto, C. M. [UNESP]; Lundberg, P.; Lerner, U. H. (Sage Publications Inc, 2010)
The osteotropic interleukin-6 (IL-6) types of cytokines IL-6, IL-11, and leukemia inhibitory factor (LIF), but not oncostatin M, are expressed by human gingival fibroblasts, and their expressions are regulated by IL-1 and tumor necrosis factor-a (TNF-alpha). In the present study, we investigated whether signaling through Toll-like receptor 2 (TLR2) can affect the expression of these cytokines in human gingival fibroblasts. Lipopolysaccharide (LPS) from P. gingivalis was found to stimulate IL-6 and LIF mRNA and protein, but not IL-11 or OSM mRNA. Using two synthetic ligands acting specifically at TLR2 and siRNA knockdown of TLR2, we demonstrated the important role of TLR2 in the stimulation of IL-6 and LIF in gingival fibroblasts. Analysis of these data suggests that signaling through the innate immune system controls the expression of osteotropic cytokines in human gingival fibroblasts.
Keywords: gingival fibroblasts; IL-6; LIF; IL-11; TLR